Use of ICT in South African Schools and the Plight of Marginalized Learners During the Covid-19 Pandemic - Nwakanma, Chinegbonkpa Hope; Adewunmi, Maryam Chinasa (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2025)
Given that information and communication technology is still a luxury for poor students, especially in developing countries like South Africa. It is crucial to examine the extent of the inequalities and social marginalisation learners face due to lack of access to ICT, as well as the impact on their learning. This study, therefore, explores the use of ICT in public schools by synthesising existing literature on its effect on the teaching and learning of socially and economically marginalised learners. Using the qualitative research approach involving document analysis and literature review, this study reveals that lack of resources, skills and the costs of the internet have worsened hardship and limited poor students’ access to ICTs and the opportunities that come with it. Findings also revealed that the South African government’s policies on ICTs and inclusive education have not been well implemented, thereby resulting in the exclusion of many students who are not privileged to attend highly ranked schools or privileged to be born in upper/middle-class homes from ICTs. It is essential to review ICT and inclusive education policies, along with effective monitoring, to ensure proper implementation as well as prevent the exclusion of underprivileged students.